PENGARUH MOTIVASI KERJA TERHADAP KINERJA PENDIDIK DAN TENAGA KEPENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 PALEMBANG - Rosiah Rosiah; Dalinur M Nur; Emi Puspita Dewi (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
This study uses quantitative research methods, which in processing the data in the form of numbers. In this study, the regression variable (X) of work motivation and variable (Y) of performance aims to determine whether motivation has an effect on the performance of educators and education staff at the state vocational high school 1 Palembang. Motivation at work can have an impact on the performance carried out, this motivation can affect the behavior of each individual at work to get maximum work results. In this study, the data was processed through a questionnaire with the number of respondents totaling 87 people, both from educators and education staff with civil servant and non-civil servant status at SMKN 1 Palembang. The data collection technique uses a questionnaire with a statement of 30 questions. The variables in this study are motivation as the independent variable (X) and performance as the dependent variable (Y). The data collected was then analyzed using a simple linear regression analysis technique by testing the test hypothesis (T) and the coefficient of determination (R2). To prove the decision-making using the SPSS For Windows Version 25 application. Based on the results of the study, it can be concluded that motivation affects the performance of educators and education staff at the Palembang 1 state vocational high school seen from the t-count value (2.965) which is greater than t- table (0.677742) with a significant level of 5% this means that H0 is rejected and Ha is accepted. Meanwhile, the percentage of the effect is 36.9% and the rest is influenced by other factors not examined in this study. Keywords: Work Motivation, Performance.